Manuel de Falla and the Spanish Musical Renaissance - James, Burnett (London Gollancz, 1979)
Mr James sees Manuel de Falla as "the most complete representative of the Spanish mind and spirit in music"; but, as the title suggests, the book is about much more than Falla. To place him in his setting, the first chapters provide a survey of Spanish music from its beginnings: folk origins; Church Music; foreign influences; comparison with musical development in other countries (especially England); Victoria and Scarlatti; Soler, Arriaga, Usandizaga; the popularity of the operetta-like Zarzuela; Albeniz, Turina, Granados.
Keywords: Falla, Manuel de -- 1876-1946; 19th Century (1801-1900); 20th Century (1901-2000); Music history; Zarzuela; Spain